Hotspots of un-iodized salt availability among Ethiopian households, evidence from the national survey data - Atalay Goshu Muluneh; Mehari W. Mariam Merid; Getahun Molla Kassa (BMC, 2023)
Abstract Background Universal salt iodization was started before decades but there are communities using the un-iodized salt till now. More than one-tenth of the Ethiopian community uses un-iodized salt. Objective This study aimed to identify the hotspots and associate factors of un-iodized salt availability in Ethiopia based on Ethiopian national household survey data. Methods We conducted an in-depth analysis of the Ethiopian Demographic and Health Survey 2016 data. A total of 15,567 households were included in the final analysis. We cleaned and weighed the data using Stata version 16 software and descriptive outputs were reported in graphs and tables. We computed the weighted prevalence of un-iodized salt and prepared it for spatial analysis. Global-level spatial autocorrelation, hotspot analysis using the Getis-Ord Gi* statistics, and spatial interpolation using empirical Bayesian interpolation were executed using ArcGIS 10.3 to predict the magnitude of un-iodized salt at the national level. The binary logistics regression model was used to identify the contributing factors of un-iodized salt utilization. Model goodness of fit was tested with Hosmer and Lemeshow goodness-of-fit test (P = 0.96). Finally, the adjusted odds ratio (AOR) with 95% CI was reported to identify significant factors. Results The magnitude of un-iodized salt availability was 14.19% (95% CI: 13.65, 14.75) among Ethiopian households. Un-iodized salt hotspots were found in Afar, Somalia, and Benishangul Gumuz regions. Compared to poorest wealth index: poorer (AOR = 0.55, 95% CI: 0.48, 0.64), middle (AOR = 0.51, 95% CI: 0.44, 0.60), richer (AOR = 0.55, 95% CI: 0.47, 0.64), and richest (AOR = 0.61, 95% CI: 0.50, 0.75); compared to uneducated household head: heads with secondary (AOR = 0.72, 95% CI: 0.60, 0.67) and above secondary (AOR = 0.54, 95% CI: 0.43, 0.67) education reduced the odds of un-iodized salt viability, while households living in highland (AOR = 1.16, 95% CI: 1.05, 1.29) had increased the odds of un-iodized salt availability. Conclusion More than a tenth of the households in Ethiopia uses un-iodized salt. Hotspots of un-iodized salt availability were found in Somali and Afar regions of Ethiopia. Better wealth index and education of the household heads reduces the odds of un-iodized salt availability while living in a high altitude above 2200 m increases the odds of un-iodized salt availability in Ethiopia.